@ -0,0 +1,123 @@ |
|||||
|
\documentclass{article} |
||||
|
\usepackage[utf8]{inputenc} |
||||
|
\usepackage{amsfonts} |
||||
|
\usepackage{amsthm} |
||||
|
\usepackage{amsmath} |
||||
|
\usepackage{amssymb} |
||||
|
\usepackage{enumerate} |
||||
|
\usepackage{hyperref} |
||||
|
\hypersetup{ |
||||
|
colorlinks, |
||||
|
citecolor=black, |
||||
|
filecolor=black, |
||||
|
linkcolor=black, |
||||
|
urlcolor=blue |
||||
|
} |
||||
|
% \usepackage{xcolor} |
||||
|
|
||||
|
% prevent warnings of underfull \hbox: |
||||
|
% \usepackage{etoolbox} |
||||
|
% \apptocmd{\sloppy}{\hbadness 4000\relax}{}{} |
||||
|
|
||||
|
\theoremstyle{definition} |
||||
|
\newtheorem{definition}{Def}[section] |
||||
|
\newtheorem{theorem}[definition]{Thm} |
||||
|
\newtheorem{innersolution}{} |
||||
|
\newenvironment{solution}[1] |
||||
|
{\renewcommand\theinnersolution{#1}\innersolution} |
||||
|
{\endinnersolution} |
||||
|
|
||||
|
|
||||
|
\title{Bilinear Pairings - study} |
||||
|
\author{arnaucube} |
||||
|
\date{August 2022} |
||||
|
|
||||
|
\begin{document} |
||||
|
|
||||
|
\maketitle |
||||
|
|
||||
|
\begin{abstract} |
||||
|
Notes taken from \href{https://sites.google.com/site/matanprasma/artifact}{Matan Prsma} math seminars and also while reading about Bilinear Pairings. Usually while reading papers and books I take handwritten notes, this document contains some of them re-written to $LaTeX$. |
||||
|
|
||||
|
The notes are not complete, don't include all the steps neither all the proofs. I use these notes to revisit the concepts after some time of reading the topic. |
||||
|
\end{abstract} |
||||
|
|
||||
|
\tableofcontents |
||||
|
|
||||
|
\section{Weil reciprocity} |
||||
|
|
||||
|
\section{Generic Weil Pairing} |
||||
|
|
||||
|
\begin{definition}{Divisor} |
||||
|
$$D= \sum_{P \in E(\mathbb{K})} n_p \cdot [P]$$ |
||||
|
\end{definition} |
||||
|
|
||||
|
\begin{definition}{Degree \& Sum} |
||||
|
$$deg(D)= \sum_{P \in E(\mathbb{K})} n_p$$ |
||||
|
$$sum(D)= \sum_{P \in E(\mathbb{K})} n_p \cdot P$$ |
||||
|
\end{definition} |
||||
|
|
||||
|
\begin{definition}{Principal divisor} |
||||
|
iff $deg(D)=0$ and $sum(D)=0$ |
||||
|
\end{definition} |
||||
|
$D \sim D'$ iff $D - D'$ is principal. |
||||
|
|
||||
|
|
||||
|
\begin{definition}{Evaluation of a rational function} |
||||
|
$$r(D)= \prod r(P)^{n_p}$$ |
||||
|
\end{definition} |
||||
|
|
||||
|
\subsection{Generic Weil Pairing} |
||||
|
Let $E(\mathbb{K})$, with $\mathbb{K}$ of char $p$, $n$ s.t. $p \nmid n$. |
||||
|
|
||||
|
$\mathbb{K}$ large enough: $E(\mathbb{K})[n] = E(\mathbb{\overline{K}}) = \mathbb{Z}_n \oplus \mathbb{Z}_n$ (with $n^2$ elements). |
||||
|
|
||||
|
$P, Q \in E[n]$: |
||||
|
$$D_P \sim [P] - [0]$$ |
||||
|
$$D_Q \sim [Q] - [0]$$ |
||||
|
We need them to have disjoint support: |
||||
|
$$D_P \sim [P] - [0]$$ |
||||
|
$$D_Q \sim [Q+T] - [T]$$ |
||||
|
|
||||
|
$$\Delta D = D_Q - D_Q' = [Q] - [0] - [Q+T] + [T]$$ |
||||
|
|
||||
|
|
||||
|
\section{Exercises} |
||||
|
\emph{An Introduction to Mathematical Cryptography, 2nd Edition} - Section 6.8. Bilinear pairings on elliptic curves |
||||
|
|
||||
|
\begin{solution}{6.29} |
||||
|
$div(R(x) \cdot S(x)) = div( R(x)) + div( S(x))$, where $R(x), S(x)$ are rational functions. |
||||
|
\\proof:\\ |
||||
|
\emph{Norm} of $f$: $N_f = f \cdot \overline{f}$, and we know that $N_{fg} = N_f \cdot N_g~\forall~\mathbb{K}[E]$,\\ |
||||
|
then $$deg(f) = deg_x(N_f)$$\\ |
||||
|
and $$deg(f \cdot g) = deg(f) + deg(g)$$ |
||||
|
|
||||
|
Proof: |
||||
|
$$deg(f \cdot g) = deg_x(N_{fg}) = deg_x(N_f \cdot N_g)$$ |
||||
|
$$= deg_x(N_f) + deg_x(N_g) = deg(f) + deg(g)$$ |
||||
|
|
||||
|
So, $\forall P \in E(\mathbb{K}),~ ord_P(rs) = ord_P(r) + ord_P(s)$.\\ |
||||
|
As $div(r) = \sum_{P\in E(\mathbb{K})} ord_P(r)[P]$, $div(s) = \sum ord_P(s)[P]$. |
||||
|
|
||||
|
So, |
||||
|
$$div(rs) = \sum ord_P(rs)[P]$$ |
||||
|
$$= \sum ord_P(r)[P] + \sum ord_P(s)[P] = div(r) + div(s)$$ |
||||
|
\end{solution} |
||||
|
|
||||
|
\vspace{0.5cm} |
||||
|
|
||||
|
\begin{solution}{6.31} |
||||
|
$$e_m(P, Q) = e_m(Q, P)^{-1} \forall P, Q \in E[m]$$ |
||||
|
Proof: |
||||
|
We know that $e_m(P, P) = 1$, so: |
||||
|
$$1 = e_m(P+Q, P+Q) = e_m(P, P) \cdot e_m(P, Q) \cdot e_m(Q, P) \cdot e_m(Q, Q)$$ |
||||
|
|
||||
|
and we know that $e_m(P, P) = 1$, then we have: |
||||
|
$$1 = e_m(P, Q) \cdot e_m(Q, P)$$ |
||||
|
$$\Longrightarrow e_m(P, Q) = e_m(Q, P)^{-1}$$ |
||||
|
\end{solution} |
||||
|
|
||||
|
|
||||
|
|
||||
|
|
||||
|
\end{document} |